1998
DOI: 10.1080/00207284.1998.11491535
|View full text |Cite
|
Sign up to set email alerts
|

Group Therapy and Organ Transplantation

Abstract: Group therapy for organ transplantation patients is in its infancy but has a promising future. Overextended transplantation service providers are interested in its potential for cost-efficient and effective forms of psychosocial intervention. This article summarizes the biomedical and psychosocial aspects of solid organ transplantation, one institution's group therapy program, common group themes, and specific demands on the group therapist working with this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 27 publications
0
12
0
2
Order By: Relevance
“…At the Toronto Hospital Multi-Organ Transplantation Program, group psychotherapy is organized along three dimensions: course of illness (pre-vs. posttransplantation), homogeneous versus heterogeneous group membership (e.g., separate groups for patients and caregivers vs. integrated groups, organ-specific groups vs. cross-organ groups), and group focus (issue-specific vs. unstructured) (Abbey and Farrow 1998). Increasing levels of group therapy intensity are used, depending on the needs of the patient.…”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…At the Toronto Hospital Multi-Organ Transplantation Program, group psychotherapy is organized along three dimensions: course of illness (pre-vs. posttransplantation), homogeneous versus heterogeneous group membership (e.g., separate groups for patients and caregivers vs. integrated groups, organ-specific groups vs. cross-organ groups), and group focus (issue-specific vs. unstructured) (Abbey and Farrow 1998). Increasing levels of group therapy intensity are used, depending on the needs of the patient.…”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…Some of the findings have suggested that non-compliance among haemodialysis patients is a complex affair which can arise from family stress, anxiety and discord [11, 12, 13]. Further variables include: malnutrition as a result of an unimaginative or incomprehensible dietary regime [12], the absence of a supervised, ongoing exercise programme [15], health beliefs and personality [6], the onset of emotional fatigue or depression [17, 18, 19], social worker input [13], participatory control of patients [20], patient reward systems [21]and counselling [22, 23, 24, 25, 26]. …”
Section: Discussionmentioning
confidence: 99%
“…This is more so if they have a pre-morbid history of mental illness [22, 23, 24, 25]. A common means to address depression and anxiety in this group of patients is to implement counselling and psychotherapy programmes.…”
Section: Treatment Strategies To Increase Compliance In Patients Recementioning
confidence: 99%
See 1 more Smart Citation
“…-Eliminar los desequilibrios psicoló-gicos de los trasplantados y sus familiares (Abbey y Farrow, 1998;Klapheke,…”
Section: Variables Psicosocialesunclassified